2009
DOI: 10.1111/j.1439-0310.2009.01648.x
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuating Asymmetry of Responders Affects Offers in the Ultimatum Game Oppositely According to Attractiveness or Need as Perceived by Proposers

Abstract: The Ultimatum Game (UG) measures cooperative tendencies in humans. A proposer offers to split a given sum of money between self and a responder, who may accept or reject the offer. If accepted, each receives the proposed split; if rejected, nobody receives anything. We studied the effect of the putative responder’s degree of facial symmetry (fluctuating asymmetry, FA) on the offer he/she received in opposite‐sexed UGs. Symmetry is an important measure of biological quality so subjects were expected to receive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…The sexual selection hypothesis has been used to explore the evolution of altruism within a variety of economic games, such as the prisoner's dilemma and the ultimatum game. Researchers have found that men and women are more altruistic and cooperative toward physically attractive players (e.g., Andreoni & Petrie, 2008;Farrelly et al, 2007;Kahn, Hottes, & Davis, 1971;Mulford, Orbell, Shatto, & Stockard, 1998;Solnick & Schweitzer, 1999;Zaatari, Palestis, & Trivers, 2009). Furthermore, offers made by women in ultimatum games are accepted more often than offers made by men (Eckel & Grossman, 2001).…”
Section: The Attractiveness Halo Effect and Altruism In Game-theoretimentioning
confidence: 99%
“…The sexual selection hypothesis has been used to explore the evolution of altruism within a variety of economic games, such as the prisoner's dilemma and the ultimatum game. Researchers have found that men and women are more altruistic and cooperative toward physically attractive players (e.g., Andreoni & Petrie, 2008;Farrelly et al, 2007;Kahn, Hottes, & Davis, 1971;Mulford, Orbell, Shatto, & Stockard, 1998;Solnick & Schweitzer, 1999;Zaatari, Palestis, & Trivers, 2009). Furthermore, offers made by women in ultimatum games are accepted more often than offers made by men (Eckel & Grossman, 2001).…”
Section: The Attractiveness Halo Effect and Altruism In Game-theoretimentioning
confidence: 99%
“…Physically attractive people are perceived to be more competent, popular, and successful than their less attractive counterparts (Langlois et al 2000) and, accordingly, should be perceived as less in need of help. Indeed, Zaatari, Palestis, and Trivers (2009) find that proposers in an ultimatum game rate the most attractive respondents as the least needy. Similarly, Fisher and Ma (2014) find that more attractive donation recipients are perceived to be less needy than less attractive recipients.…”
Section: Want Versus Should Preferences In Charitable Givingmentioning
confidence: 99%
“…Perceptions of beauty and neediness are often negatively correlated (Fisher and Ma 2014;Langlois et al 2000;Zaatari, Palestis, and Trivers 2009); therefore, a focus on beauty could result in neglect of the neediest individuals.…”
mentioning
confidence: 99%
“…For example, prosocial biases in favor of physically attractive people have been observed in door-to-door fundraising (Landry, Lange, List, Price, & Rupp, 2006) and charitable donation behavior (Price, 2008; Raihani & Smith, 2015). Effects of facial attractiveness on prosocial decisionmaking have been observed in laboratory settings using economic game-theoretical paradigms: attractive people were offered more money, compared to unattractive players (Rosenblat, 2008; Solnick & Schweitzer, 1999) as signaled for instance in higher facial asymmetry (Zaatari, Palestis, & Trivers, 2009). Interestingly, physically attractive people themselves are actually less generous, less cooperative and less trustworthy (Maestripieri et al, 2017), suggesting that although we reliably infer traits about people from their faces, these judgments are often not valid.…”
Section: Faces and Prosocial Behaviormentioning
confidence: 99%